A TAXONOMIC REVISION OF THE CHILEAN GROTEINI (Acta Entomológica Chilena, 2022)
The South American ichneumonid genera Echthropsis Brélhes and Macrogrotea Brélhes have 6 endemicspecies in mediterranean and valdivian Chile, whose closest relatives inhabit the Andean Puna andCloud Foreslsof Perú. Eehthropsis (without a genal processjcontainsf. gayt (Spinola). with the ovipositorlonger than the gasler, and £. curten sp. nov., whose ovipositor is half as long as the gaster. Macrogrotea isrepresented by Af. mperba (Schmiedeknecht), with vertical genalleelh; by Af. ebúrnea, sp. nov., with genalleeth turned mesad over the buccal cavity bul well separated; by Af. onetlh sp. nov., whose ovipositoraverages 0.65 l'ore wing length and whose genal leeth are transformed into horizontal processes ofwhich ihe trúncate ápices meet on the mid-lineof the buccal cavity; as well as by Ai. chiloe sp. nov., like Af.imetlli in its genal processes bul distinct by its ovipositor length (averages 0.80 fore wing length).The Tribe Groteini, as recognized here, ineludes the New World genera Crotea, Macrogrotea, andEehthropsis, huí exeludes the Australian and Brasilian Labium Brullé.
Keywords: Ichneumonid wasps, Hymenoptera, Groteini. Chile, Taxonomv